Impact of intensity modulated radiation therapy on survival in anal cancer - Jhaveri, Jaymin; Rayfield, Lael; Liu, Yuan; Chowdhary, Mudit; Tian, Sibo; Cassidy, Richard J.; Gillespie, Theresa; Patel, Pretesh R.; Landry, Jerome C.; Patel, Kirtesh R. (Journal of Gastrointestinal Oncology; Vol 9, No 4 (August 01, 2018): Journal of Gastrointestinal Oncology, 2018)
Background: This study was designed to investigate the impact of intensity modulated radiation therapy (IMRT) on overall survival (OS) in patients treated with chemoradiation (CRT) for anal cancer (AC). Methods: We performed a case-control, propensity score (PS) matched analysis of the National Cancer Data Base (NCDB) of patients diagnosed with non-metastatic AC from 2004 to 2013. Only patients receiving concurrent CRT were included. Patients were stratified into two groups based on the RT technique: IMRT vs. non-IMRT. Multivariate analysis (MVA) and Kaplan-Meier (KM) plots for OS were obtained for the matched and unmatched groups. Results: A total of 8,108 patients diagnosed between 2004 and 2013 were eligible for the study, of which 3,307 (40.8%) and 4,801 (59.2%) were in the IMRT and non-IMRT groups, respectively. Median follow-up for all patients was 54.4 months. After PS matching, MVA for OS showed that IMRT was associated with improved OS compared to non-IMRT (HR 0.83, 95% CI: 0.74–0.94; P=0.002). Adjusted KM analysis showed that the 5-year OS for patients treated with IMRT was 74.6% vs. 70.5% (P=0.0022). Conclusions: To our knowledge, this is the largest study to date that evaluates the impact of IMRT on OS for patients with AC. Our investigation shows that IMRT based concurrent CRT for non-metastatic AC is associated with improved survival when compared to similar patients treated with non-IMRT based therapy. In the absence of randomized evidence, our analysis might provide additional support for increasing the use of IMRT for patients with AC receiving concurrent CRT.